Compared to the efficiency of the liquidation of drinking water between two stations in the city of Mosul - Afaf Abdullah; ammar Ameen (College of Education for Pure Sciences, 2007)
The present study was aimed to compare between tow plants of Mosul station .one is locate in the north of the city center which called AL_koba plant station before the Tigris river passing mosul city at the right bank of the river , which supply the west part of the city by drink water . The second plant station which called AL dan dan section in the center of mosul city ,at the left bank of Tigris river which supply some of the east part like AL ~mansour . The samples were collected during the period between April 2001 and August 2001 from four location as follows:near water resorce at river bank ,prespitation zone ,coloration zone and supply of water zone Then we do the chemical,physical and biological testes in order to study its suitable for drinking purposes .we saw after study that Alkoba plant more effective in the removal of the turbidity and oranig matter than the dandan plant.